Distribución de la vegetación en las ruinas mayas y su relación con el uso de la tierra en la antiguedad en Lamanai, Belice - Lambert, J.D.H; Arnason, T (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
A quantitative analysis of forest vegetation at the ancient Maya settlement of Lamanai (ca 300BC - AD 1640) was undertaken to determine the relationship between extant vegetation and the major and minor ruins. Five associations sere distinguished: Shore Line, Cohune Ridge, High Bush, Bajo and Ruin. The Ruin association, dominated by Brosinum alicastrum, Protium copal, Talisia oliviformis and Pimenta dioica, was unique. Present day Maya residents view the occurrence of Cohune as an indicator of good land for their milpa operations. Soil analyses indicate that the Cohune Ridge and Bajo associations would be suitable for agriculture. A sediment core taken from a nearby lake revealed that burning was common in ancient times. Two layers (95 and 28 cm) contained large amounts of carbonized plant fragments.